Barrett's Esophagus: A Comprehensive and Contemporary Review for Pathologists - Naini, Bita V; Souza, Rhonda F; Odze, Robert D (The American journal of surgical pathology, 2016)
This review provides a summary of our current understanding of, and the controversies surrounding, the diagnosis, pathogenesis, histopathology, and molecular biology of Barrett's esophagus (BE) and associated neoplasia. BE is defined as columnar metaplasia of the esophagus. There is worldwide controversy regarding the diagnostic criteria of BE, mainly with regard to the requirement to histologically identify goblet cells in biopsies. Patients with BE are at increased risk for adenocarcinoma, which develops in a metaplasia-dysplasia-carcinoma sequence. Surveillance of patients with BE relies heavily on the presence and grade of dysplasia. However, there are significant pathologic limitations and diagnostic variability in evaluating dysplasia, particularly with regard to the more recently recognized unconventional variants. Identification of non-morphology-based biomarkers may help risk stratification of BE patients, and this is a subject of ongoing research. Because of recent achievements in endoscopic therapy, there has been a major shift in the treatment of BE patients with dysplasia or intramucosal cancer away from esophagectomy and toward endoscopic mucosal resection and ablation. The pathologic issues related to treatment and its complications are also discussed in this review article.